Combined effects of salinity changes and salicylic acid exposure in Mytilus galloprovincialis - Freitas, Rosa (2021)
Pharmaceuticals and Personal care products (PPCPs) are frequently released into several marine matrices, representing significant environmental and ecotoxicological risks. Among the widest spread PPCPs in aquatic systems is Salicylic acid (SA), with known negative effects on marine and freshwater species. Nevertheless, the toxicity resulting from these emerging pollutants, including SA, together with climate change has still received little attention up to date. Among climate change related factors salinity is one that most affects aquatic organisms. To better understand the combined impacts of SA and salinity, the present study evaluated the biochemical alterations induced in Mytilus galloprovincialis mussels exposed to SA and different salinity levels, acting individually and in combination. The effects observed clearly highlighted that cellular damages were mainly observed at higher salinity (35), with no additive or synergistic effects derived from the combined presence of SA. Higher antioxidant capacity of mussels in the presence of SA may prevent increased LPO levels in comparison to uncontaminated mussels. Nevertheless, in the presence of SA mussels revealed loss of redox balance, regardless of the salinity level. Furthermore, mussels exposed to SA at control salinity showed increased metabolic capacity which decreased when exposed to salinities 25 and 35. These findings may indicate the protective capacity of mussels towards higher stressful conditions, with lower energy reserves expenditure when in the presence of SA and salinities out of their optimal range. Although limited cellular damages were observed, changes on mussel's redox balance, antioxidant mechanisms and metabolism derived from the combined exposure to SA and salinity changes may compromise mussel's growth and reproduction. Overall, the present study highlights the need to investigate the impacts induced by pollutants under present and future climate change scenarios, towards a more realistic environmental risk assessment.